Cytochrome P450-2E1 is involved in aging-related kidney damage in mice through increased nitroxidative stress. (November 2017) - Abdelmegeed, Mohamed A.; Choi, Youngshim; Ha, Seung-Kwoon; Song, Byoung-Joon
Abstract: The aim of this study was to investigate the role of cytochrome P450-2E1 (CYP2E1) in aging-dependent kidney damage since it is poorly understood. Young (7 weeks) and aged female (16–17 months old) wild-type (WT) and Cyp2e 1-null mice were used. Kidney histology showed that aged WT mice exhibited typical signs of kidney aging such as cell vacuolation, inflammatory cell infiltration, cellular apoptosis, glomerulonephropathy, and fibrosis, along with significantly elevated levels of renal TNF-α and serum creatinine than all other groups. Furthermore, the highest levels of renal hydrogen peroxide, protein carbonylation and nitration were observed in aged WT mice. These increases in the aged WT mice were accompanied by increased levels of iNOS and mitochondrial nitroxidative stress through altered amounts and activities of the mitochondrial complex proteins and significantly reduced levels of the antioxidant glutathione (GSH). In contrast, the aged Cyp2e1 -null mice exhibited significantly higher antioxidant capacity with elevated heme oxygenase-1 and catalase activities compared to all other groups, while maintaining normal GSH levels with significantly less mitochondrial nitroxidative stress compared to the aged WT mice. Thus, CYP2E1 is important in causing aging-related kidney damage most likely through increasing nitroxidative stress and that CYP2E1 could be a potential target in preventing aging-related kidney diseases. Highlights: The role of CYP2E1 in aging-related kidney damage is largely unknown. Young and aged female wild-type (WT) and Cyp2e 1-null mice were evaluated. Aged WT mice exhibited highest levels of inflammation, nitroxidative stress, apoptosis, and fibrosis. Cyp2e1 -null mice were resistant to aging-related kidney damage partly due to high levels of antioxidant capacity. CYP2E1 is important in mediating aging-related kidney damage.